Developing a Canadian framework for social determinants of health and well-being among children with neurodisabilities and their families: an ecosocial perspective. Issue 26 (18th December 2021) - Filipe, Angela M.; Bogossian, Aline; Zulla, Rosslynn; Nicholas, David; Lach, Lucyna M.
Abstract: Purpose: Social Determinants of Health is a conceptual framework typically used to understand patterns of health and ill-health at the population level. Its applicability to children and youth who already have a health condition, in this case, a neurodisability, is not well understood, particularly when the "health" component of that framework is extended to include more pluralistic notions of well-being. The purpose of this study was to address this challenge and to develop an ecosocial framework that is conceptually integrative and meaningful to children and youth with neurodisabilities and their families. Methods: Drawing on a critical literature review, a conceptual analysis approach, and a secondary analysis of a compendium of 36 social determinants of health models, we critically analysed how these models map onto the context of childhood neurodisability and identified key conceptual and empirical challenges. The emerging framework was further validated through iterative stakeholder consultation with parents, self-advocates, researchers, practitioners, community leaders, and decision-makers. Results: The review and consultation process generated The Canadian Framework for Social Determinants of Health and Well-being among Children with Neurodisabilities and their Families. This new framework consists of two hemispheres encompassing explanatory (or observational) and action-oriented (or transformational) components relating to social determinants of health and well-being and living a daily life of quality in childhood neurodisability. Conclusion: The proposed framework provides a roadmap for practitioners, policy-makers, and researchers as well as activists, families, and communities, to reflect on both social determinants and social change processes that shape the health, well-being, and everyday lives of children and youth with neurodisabilities and their families. IMPLICATIONS FOR REHABILITATION: Social Determinants of Health provides a conceptual framework for understanding the social causes and consequences of health and ill-health at the population level. In childhood neurodisability, however, it is important to consider pluralistic notions of "well-being" and living a daily "life of quality" that may relate, but are not limited, to health. The Canadian Framework for Social Determinants of Health and Well-being among Children with Neurodisabilities and their Families comprises an explanatory hemisphere of social determinants, factors, and contingencies, and an action-oriented hemisphere that identifies different forms and levels of mobilization that can guide rehabilitation practice to achieve social change in the lives of children, youth, and their families. Using an ecosocial perspective, this framework provides a roadmap for future research and policy development that is relevant to children and families as well as to current perspectives in rehabilitation, social and health justice, and childhood, disability, and neurodiversity rights.